2015
DOI: 10.4314/jfas.v1i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry characterization of ferrocene/ferricenium redox couple at glassycarbon electrode

Abstract: In the present work the oxidation of ferrocene, ( ) , to the ferrocenium cation, ( ) , was examined in the solvents dichloromethane, and aqueous ethanol using the technique of cyclic voltammetry. The anodic (Epa) and the cathodic (Epc) peak potentials, as well as the corresponding anodic (ipa) and cathodic (ipc) peak currents, were obtained at different scan rates (0.05, 0.10, 0.30, 0.50 V.s -1 ). The diffusion coefficients (D) have been calculated using the Randles-Sevcik equation. The effects of changing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 4 publications
(4 reference statements)
1
16
0
Order By: Relevance
“…The potential of peak P1 is pH-independent. Comparing to the literature data, peak P1 can be ascribed to the following charge transfer reaction [Fe II (C5H5)2] ⇌ [Fe III (C5H5)2] + + e − [44,48]. The forward and backward components of peak P1 are oxidative and reductive currents, respectively (see inset in Figure 2), which indicates that the oxidation of ferrocene is reversible electrode reaction.…”
Section: Electrochemical Properties Of Selected Compounds By Voltammesupporting
confidence: 50%
See 1 more Smart Citation
“…The potential of peak P1 is pH-independent. Comparing to the literature data, peak P1 can be ascribed to the following charge transfer reaction [Fe II (C5H5)2] ⇌ [Fe III (C5H5)2] + + e − [44,48]. The forward and backward components of peak P1 are oxidative and reductive currents, respectively (see inset in Figure 2), which indicates that the oxidation of ferrocene is reversible electrode reaction.…”
Section: Electrochemical Properties Of Selected Compounds By Voltammesupporting
confidence: 50%
“…[Fe III (C 5 H 5 ) 2 ] + + e − [44,48]. The forward and backward components of peak P1 are oxidative and reductive currents, respectively (see inset in Figure 2), which indicates that the oxidation of ferrocene is reversible electrode reaction.…”
Section: Electrochemical Properties Of Selected Compounds By Voltammementioning
confidence: 99%
“…In general, the cathodic behavior ferrocene usual in organic media such as dichoromethane, acetonitrile and DMF can be described by a reversible reduction in an electron, leading to ion Ferrocerium [1]. In the present work the oxidation of ferrocene, Fe(C 5 H 5 ) 2 , to the ferrocenium cation, Fe(C 5 H 5 ) 2 + , was examined in the solvents dichloromethane solution containing tetrabutylammonium tetrafluoroborate , and aqueous solution containing sulfuric acid using the technique of cyclic voltammetry [2,3]. The results indicated that redox reactions of ferrocene/ ferricenium couple were a reversible process of diffusion-controlled single electron transfer in both studied solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Where X corresponds to ΔE p at different scan rates. The electroactive area was calculated according to the Randles-Sevcik [45][46][47] (Equation 4) equation. The electrode was subjected to cyclic voltammetry technique in…”
Section: Electrochemical Study Of Modified Electrodesmentioning
confidence: 99%